2020
DOI: 10.3390/plants9101313
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Allelochemicals in Miscanthus sacchariflorus Extracts and Assessment of Their Effects on Germination and Seedling Growth of Common Weeds

Abstract: There is increasing interest in the application of bioherbicides because they are less destructive to the global ecosystem than synthetic herbicides. Research has focused on reducing the dependence upon synthetic herbicides by substituting them with environmentally and economically sustainable bioproducts. Allelopathic phytochemicals may be an efficient method for controlling weeds, benefitting both the environment and human health. This study addressed the allelopathic potential of Miscanthus sacchariflorus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 100 publications
2
18
0
Order By: Relevance
“…Studies on different weed species have shown that allelochemicals toxicity leads to degradation of chlorophyll, decrease in starch accumulation, and interference in the size and number of chloroplasts. 42 A study conducted on broad leaf weed (Rumex acetosa) showed that at higher ferulic and p-hydroxybenzoic acids levels, photosynthetic machinery and photosystem II photochemistry were significantly decreased, compared to control. 43 Reduction in photosynthetic pigments and functions were also highly decreased in maize seedlings after treatment with Nicotiana plumbaginifolia Viv., as demonstrated by Singh et al 44 By targeting photosynthetic pigments and carotenoids (chlorophyll a, chlorophyll b, ⊎-carotene, lutein, neoxanthin, and violaxanthin) to identify allelochemicals stress responses in monocot and dicot weeds, we focused on different germination and seedling growth traits under the various planting densities.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on different weed species have shown that allelochemicals toxicity leads to degradation of chlorophyll, decrease in starch accumulation, and interference in the size and number of chloroplasts. 42 A study conducted on broad leaf weed (Rumex acetosa) showed that at higher ferulic and p-hydroxybenzoic acids levels, photosynthetic machinery and photosystem II photochemistry were significantly decreased, compared to control. 43 Reduction in photosynthetic pigments and functions were also highly decreased in maize seedlings after treatment with Nicotiana plumbaginifolia Viv., as demonstrated by Singh et al 44 By targeting photosynthetic pigments and carotenoids (chlorophyll a, chlorophyll b, ⊎-carotene, lutein, neoxanthin, and violaxanthin) to identify allelochemicals stress responses in monocot and dicot weeds, we focused on different germination and seedling growth traits under the various planting densities.…”
Section: Discussionmentioning
confidence: 99%
“…Allelopathy reduces and disrupts the germination of crop seeds and restricts the growth of shoots and roots [ 21 ]. Most of the plant physiological mechanisms such as photosynthesis, functions of membranes and enzymes, water and nutrient uptake and germination of seedlings are influenced by allelochemicals [ 22 , 23 ]. Moreover, phytochemicals may be applied as bioherbicides to increase crop production by means of biological weed management through allelopathy.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the proliferation of weeds and the abuse of chemical herbicides, an increasing number of allelopathic plants have been found to inhibit the growth of harmful weeds. For instance, Ficus carica suppresses Peganum harmala and Silybum marianum ( Ladhari et al, 2020 ), allelopathic rice significantly inhibits E. crusgalli ( Li et al, 2020 ), and Miscanthus sacchariflorus can also suppress weed growth ( Ghimire et al, 2020 ). In our previous study, field observation and laboratory experiments have confirmed that A. argyi is an ecologically dominant population and can also be used for weed control.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, an increasing number of studies have examined the application of allelochemicals in plants to effectively control weed growth in recent years ( Iqbal et al, 2016 ; Ladhari et al, 2018 ). These plant-derived allelochemicals have been widely studied because of their advantages of environmental friendliness, low toxicity, easy degradation and lack of residue ( Ghimire et al, 2020 ). Thus, it is of great significance to clarify the allelochemicals secreted by A. argyi and their molecular mechanism for elucidating its ecological advantages and regulating the ecological balance.…”
Section: Introductionmentioning
confidence: 99%